2016
DOI: 10.1177/1744806916649191
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid 1 receptor knockout mice display cold allodynia, but enhanced recovery from spared-nerve injury-induced mechanical hypersensitivity

Abstract: BackgroundThe function of the Cannabinoid 1 receptor (CB1R) in the development of neuropathic pain is not clear. Mounting evidence suggest that CB1R expression and activation may contribute to pain. Cannabinoid 1 receptor knockout mice (CB1R−/−) generated on a C57Bl/6 background exhibit hypoalgesia in the hotplate assay and formalin test. These findings suggest that Cannabinoid 1 receptor expression mediates the responses to at least some types of painful stimuli. By using this mouse line, we sought to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…The role of TRPM8 in the development of cold hypersensitivity has been demonstrated previously in animal and human CIPN studies (Gauchan et al, 2009; Kono et al, 2012; Ta et al, 2010). A recent study showed that global CB1R deletion exaggerated the responses to hindpaw cold stimulation in naive and neuropathic mice suggesting that CB1R activation may protect against the development of cold allodynia (Sideris et al, 2016). In contrast, other studies have demonstrated a lack of such effects of CB1R deletion on cold sensitivity before and after induction of neuropathy (Castane et al, 2006; Deng et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The role of TRPM8 in the development of cold hypersensitivity has been demonstrated previously in animal and human CIPN studies (Gauchan et al, 2009; Kono et al, 2012; Ta et al, 2010). A recent study showed that global CB1R deletion exaggerated the responses to hindpaw cold stimulation in naive and neuropathic mice suggesting that CB1R activation may protect against the development of cold allodynia (Sideris et al, 2016). In contrast, other studies have demonstrated a lack of such effects of CB1R deletion on cold sensitivity before and after induction of neuropathy (Castane et al, 2006; Deng et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, CB1R has been identified as a viable candidate in controlling pain and inflammation (Kunos et al, 2009;Milligan et al, 2020). Global CB1R KO studies have demonstrated the necessity of CB1R action for both endogenous and therapeutically induced pain inhibition (Sideris et al, 2016;Bajic et al, 2018). Although these studies have established the analgesic function of CB1R, they have failed to distinguish the most critical loci for analgesic action.…”
Section: Contributions Of Autoantibodies and Neuronal Fcc Receptors To Joint Pain In Arthritismentioning
confidence: 99%
“…The earliest studies describing the importance of the eCB system in the modulation of pain behaviors came from global deletion of the CB1 receptor, 94 which revealed receptor modulation of thermal and tactile sensitivity, and reinforcing properties of opioids. 94–97 Pharmacological studies using brain-impenetrant or site-specific injections of drugs and conditional knock out mouse studies have revealed that peripheral, spinal, and supraspinal sites are involved in cannabinoid-mediated analgesia. 98–103…”
Section: Endocannabinoid System and Pain Modulationmentioning
confidence: 99%